ダイ 30 ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1989 - 首藤, 康雄; シュドウ, ヤスオ; 福山, 佳之; フクヤマ, ヨシユキ; 加藤, 美雄; カトウ, ヨシオ; 宮本, 仁美; ミヤモト, ヒトミ; Shudo, Yasuo; Fukuyama, Yoshiyuki; Kato, Yoshio; Miyamoto, Hitomi (1991)
P(論文) この報告は, 第30次南極地域観測隊越冬隊気象部門が, 1989年2月1日から1990年1月31日までの1年間, 昭和基地において行った気象観測の結果をまとめたものである。観測項目・方法は第29次観測隊と同じであるが, 地上気象観測および高層気象観測については総合自動気象観測装置の更新を行った。越冬期間中に特記される気象現象としては, 次のものがあげられる。1) 5月の月平均気温は, -21.1℃を記録し, 月平均気温の最低値を更新した。2) 南極オゾンホール現象に伴う顕著なオゾン全量の減少が9月下旬から10月中旬に観測され, 9月から11月までの月平均オゾン全量は当該月の3番目に少ない値となった。3) 発達した低気圧が昭和基地に接近し, 2月3日には, 最大風速41.6m/s, 最大瞬間風速50.8m/sを記録し, 月の第1位の記録を更新した。 This paper describes the results of meteorological observations at Syowa Station from February 1,1989 to January 31,1990 carried out by Meteorological Observation Team of the 30th Japanese Antarctic Research Expedition. The new data processing system (AMOS-2 : Automated Meteorological Observation System 2) was set up in January 1989,and the automated upper-air observation and surface observation by means of this system began in February 1989. Remarkable characteristics are as follows. 1) Monthly mean temperature of May was -21.1℃, which was the minimum record in May for the total period of observation. 2) Extremely low amount of total ozone was observed for the period of late September through mid October. Monthly mean amounts of total ozone in September, October and November recorded the third lowest in those months since 1961. These results showed the influence of the Antarctic ozone hole. 3) Strong cyclone hit our station and strong wind blew on February 3. Maximum wind speed and maximum peak gust were 41.6m/s and 50.8m/s, respectively, which were maximum records in February for the total period of observation. departmental bulletin paper